A Risk-Based Bank Rating: Studi Multi Kasus pada Perbankan Syariah - Rofiqoh, Siti Nur Indah; Ratnasari, Ririn Tri; Rufaidah, Anik; Hasib, Fatin Fadhilah (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2022)
This paper aims to explain the internal and external factors on the credit risk that represented by Non-Performing Financing (NPF) of sharia bank. Internal variables related to Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR). Return on Assets (ROA), Operating Expenses Ratio (OER), Investment Proportion and Risk (IPR), Profit and Loss Sharing (PLS) as financing ratio. External variables related to Gross Domestic Product (GDP) by industrial origin. The annual data report of Statistik Perbankan Syariah (SPS) and Statistik Ekonomi Keuangan Indonesia (SEKI) in Indonesia as secondary data is used to support priority setting of SWOT analysis element to complete IFAS dan EFAS after the multiple regression analysis. Different with the result of regression t and f-Statistic analysis, the finding indicated that internal variables more influence than external variable on the credit risk based on SWOT priority analysis. The most influence variable on the credit risk is increasing Operating Expenses Ratio (OER). The limitations of this paper are expected to have difference implication for SPS, the sharia compliance from regulator management and the important role of SPS and SEKI.